Hechtia mapimiana (Bromeliaceae; Hechtioideae), a new species from the state of Durango, Mexico - López-Ferrari, Ana Rosa; Espejo-Serna, Adolfo (Instituto de Ecología, A.C., 2013)
Hechtia mapimiana a new endemic species from Cañón de Fernández, sierra de Mapimí, in the state of Durango, Mexico, is described and illustrated. The new taxon is compared with H. zamudioi, species with similar vegetative and floral characteristics.